Helminths of Steindachnerina insculptain two distinct stretches of the Taquari River, state of São Paulo,Brazil - Acosta, Aline Angelina [UNESP]; Queiroz, Jamile [UNESP]; Brandão, Heleno [UNESP]; Carvalho, Edmir Daniel [UNESP]; Silva, Reinaldo Jose Da [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2013)
The purpose of this study was to evaluate the helminth fauna ofSteindachnerina insculpta in the Taquari River, a tributaryof the Jurumirim reservoir in the state of São Paulo, and to investigate whethersome helminth species may act as a bioindicator of environmental impact. Thehost fish sample was composed of 60 specimens, with 30 individuals sampled in alotic stretch and 30 in a lentic stretch. The following were found: themonogeneans Anacanthoroides mizelli, Diaphorocleidus kabatai,Urocleidoides sp. and Euryhaliotrema chaoi; thedigenean Sphincterodiplostomum musculosum and unidentifiedmetacercariae; the nematode Travnema travnema and unidentifiedlarvae; and the acanthocephalan Gorytocephalus plecostomorum.The total prevalence of monogeneans (z = 3.14; p =0.002) and A. mizelli (z = 3.879; p ≤0.001), as well as the mean abundance of total monogeneans (U =642.0; p ≤ 0.001) and A. mizelli (U =623.5; p ≤ 0.001), were higher in the lentic stretch.Steindachnerina insculpta and its monogeneans comprise apotential group that could be used to investigate environmental impact, asdemonstrated in this study.

O objetivo desde estudo foi avaliar a helmintofauna deSteindachnerina insculpta no rio Taquari, um tributário doreservatório de Jurumirim, estado de São Paulo, e verificar se algumaespécie pode agir como bioindicadora de impacto ambiental. A amostragem depeixes foi composta de 60 espécimes, com 30 indivíduos amostrados notrecho lótico e 30 no trecho lêntico. Foram encontrados osmonogenóides: Anacanthoroides mizelli, Diaphorocleidus kabatai,Urocleidoides sp. e Euryhaliotrema chaoi; odigenético Sphincterodiplostomum musculosum e metacercárias nãoidentificadas, o nematoide Travnema travnema e larvas nãoidentificadas; e o acantocéfalo Gorytocephalus plecostomorum. Aprevalência total de monogenóides (z = 3,14; p =0,002) e A. mizelli (z = 3,879; p ≤0,001) e também a abundância média de monogenóides total(U = 642,0; p ≤ 0,001) e A. mizelli (U= 623,5; p ≤ 0,001) foram maiores no trecho lêntico.Steindachnerina insculpta e seus monogenóidescompõem um grupo em potencial que pode ser usado para investigar impactosambientais, como mostrado neste estudo.
Helmintos de Steindachnerina insculpta em doistrechos distintos do rio Taquari, Estado de São Paulo, Brasil
Keywords: Neotropical fish; teleost; parasites; bioindicator; reservoir; Peixes Neotropicais; teleósteos; parasitas; bioindicador; reservatório